Massive posterior cranial vault erosion and its reconstruction: A peculiar presentation of "mega cisterna magna" - Adity Bansal; Gosla Srinivas Reddy; Ashi Chug; Sriram Chandra Damaraju (Elsevier, 2021)
Dandy-Walker (DW) complex is a rare central nervous system malformation, commonly associated with complex non-neurological conditions, defined by four variants with characteristic anatomic features, still inadequately known for its etiological aspects. "Mega Cisterna Magna" (MCM) is a type of DW complex which is represented by an enlarged posterior cranial fossa. Though reduction cranioplasty has been reported in enlarged posterior cranial fossa malformations, however we report a peculiar case of MCM with massive posterior cranial bone erosion, presenting completely asymptomatic at an age of 8 years, without any associated co-morbidities till date, nor with any evident occipital mass at birth. Survival of the child till this age is an exception in itself, but this can probably be explained by the presence of the giant defect of the posterior cranial bone, which must have acted like a vent and prevented the elevation of the ICP. Hence no symptoms were observed till date. Ventriculo-peritoneal (VP) shunting was done to drain the accumulated fluid, followed by massive cranioplasty, which was challenging and was performed with autologous cranial and fibular bone grafts, along with alloplastic titanium mesh, and thus achieving marked aesthetic improvement with satisfactory bone healing at a 3-year follow-up.